The Snouck Hurgronje’s Doctrine in Conquering the Holy Revolts of Acehnese Natives - Chairul Fahmi (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2021)
This article aims to analyze the role of Christian Snouck Hurgronje in Aceh warfare (1873-1902). Snouck Hurgronje was involved in the Dutch war in Aceh by advising military chiefs of the best approach to conquer the insurgency in the Aceh region. The article is qualitative research, in which data is primarily extracted from secondary resources, such as books, journals, and other related sources on this topic. The paper found that after the Dutch declared war on Aceh on 26th March 1873, they were exhausted and lost against the Acehnese revolt. The Dutch government finally recruited an Islamic and Oriental expert from Leiden University, Prof Christian Snouck Hurgronje, to find the best way to conquer the rebellion in Aceh. This recruitment was also intertwined with the academic motivation of Hurgronje to understand Islam and its society of Aceh. Accordingly, Hurgronje suggested that the best solution to end the Acehnese resistance was by establishing a good partnership with the Acehnese royal chiefs called ‘Uleebalang’ on the one hand and demolishing the resistance groups that led by the ulama (Islamic scholars) groups on the other hand. Snouck Hurgronje believed that the ulama was the most radical Islamic institution who led a holy war against the Dutch colonial regime in Aceh. As a result, the Dutch military chief interpreted his recommendation by deploying all resources to hunt and execute the ulama and their followers. In some cases, this military operation caused a genocide of innocent peoples such as women, the elderly, and children.